The role of the school counselor as an energizing agent in the educational and social scenario - Morales-Carrero, Jesús (Innovaciones Educativas, 2020)
The role of the school counseling professional as an energizing agent of the educational process has experienced a special upswing in the 21st century. This has occurred because the educational setting, being the place of confluence of various social and cultural practices, has become a space saturated with controversies, as well as problematic situations. These warrant the use of intervention strategies that promote the appropriate conditions so that the student and the other educational actors are able to resolve, either by themselves or with the cooperation of third parties, personal, emotional, affective, educational and social conflicts. In response to these requirements, it is intended to achieve a theoretical review that hints at the relevance of the school-counseling professional as an actor in the educational system. This counselor should be capable of promoting the multidimensional development of other participants through the promotion and learning of social skills such as: empathetic attitudes, the peaceful resolution of controversies, decision-making and cooperation. These are practices that, due to their relevance, favor the formation of citizens with a broad sense of belonging, participation and with the vocation to transform their reality and that of others. Therefore, the role of the counselor should focus on promoting the means to survive in adverse conditions, stress, frustrations and hostile environments, conflictive situations that due to their high level of recurrence afflict the human being today.